Behavior of hybrid FRP-concrete-steel multitube hollow columns under axial compression. (30th August 2020) - Li, L.J.; Fang, S.; Fu, B.; Chen, H.D.; Geng, M.S.
Highlights: Concrete filled in a small-diameter FRP tube shows to have an ultra-high strength and axial strain. The proposed MTHCs possess a high load capacity and excellent ductility. A large rupture strain FRP outer tube could maximize the performance of the proposed MTHCs. Abstract: Hybrid use of fiber reinforced polymer (FRP) composites with conventional construction materials offers an ample opportunity to develop economical and high-performance structures. A typical example is the hybrid FRP-concrete-steel double-skin tubular columns (DSTCs), which consist of an outer FRP tube and an inner steel tube, with the space between filled with concrete. This paper presents the conceptional development of a variation of the DSTC by replacing part of concrete sandwiched between the outer and inner tubes with a number of small-diameter concrete-infilled FRP tubes [referred to as "hybrid FRP-concrete-steel multitube hollow columns (MTHCs)"]. The small-diameter concrete infilled FRP tubes possess ultra-high strength and excellent deformability due to the effective confinement, thus enabling the novel form of columns to have an excellent structural performance. Results of tests on seven stub columns are presented in this paper, confirming some expected advantages of the proposed MTHCs. Test results also suggested that MTHCs usually fail by the hoop rupture of the outer FRP tube, and a large rupture strain FRP tube used as the outer tube could lead to a higher utilization rate of the tensile strength of inner CFPR tubes and thus an even better performance for MTHCs.